TINDAK TUTUR ILOKUSI DALAM TALKSHOW MATA NAJWA PADA MEDIA SOSIAL YOUTUBE EDISI JULI-SEPTEMBER 2022 - Hesti Yulia Rahmawati; Imam Safii (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2023)
Illocutional Actions in Mata Najwa Talkshow on Youtube Social Media, July–September 2022 Edition. A speech act is a speech behavior that will affect the effectiveness of communication. The purpose of this study was to describe the illocutionary speech acts contained in the video talkshow Mata Najwa on the July–September 2022 edition of YouTube social media. The method used in this research is descriptive qualitative with content analysis. The source of the data used in this study was the video talk show Mata Najwa on the social media site Youtube. The data for this study is in the form of illocutionary speech acts contained in the video talk show using Austin's theory. The results of the data found were 3 assertive speech acts, 9 directive speech acts, 2 declarative speech acts, 3 commissive speech acts, and 7 expressive speech acts. The results of this study can be used as a medium for learning to speak Indonesian. For example, in story reading material as well as news reading material.